2021
DOI: 10.1128/spectrum.00833-21
|View full text |Cite
|
Sign up to set email alerts
|

Nitrospina -like Bacteria Are Dominant Potential Mercury Methylators in Both the Oyashio and Kuroshio Regions of the Western North Pacific

Abstract: MeHg is highly neurotoxic and accumulates in marine organisms. Thus, understanding MeHg production in seawater is critical for environmental and human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Kagoshima Bay contains acidic seawater because of hydrothermal activity, which renders this region globally unique. , Previously, we observed that the mercury concentration of the seawater here is higher at greater depths owing to the development of a thermocline from August to October . It has also been suggested that nitrite-oxidizing bacteria present in seawater convert mercury to methylmercury . Methylmercury is highly toxic and bioaccumulative, and its accumulation in humans through the consumption of contaminated fish and shellfish causes Minamata disease.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Kagoshima Bay contains acidic seawater because of hydrothermal activity, which renders this region globally unique. , Previously, we observed that the mercury concentration of the seawater here is higher at greater depths owing to the development of a thermocline from August to October . It has also been suggested that nitrite-oxidizing bacteria present in seawater convert mercury to methylmercury . Methylmercury is highly toxic and bioaccumulative, and its accumulation in humans through the consumption of contaminated fish and shellfish causes Minamata disease.…”
Section: Resultsmentioning
confidence: 68%
“…45 It has also been suggested that nitrite-oxidizing bacteria present in seawater convert mercury to methylmercury. 46 Methylmercury is highly toxic and bioaccumulative, and its accumulation in humans through the consumption of contaminated fish and shellfish causes Minamata disease. Therefore, understanding its behavior in seawater is important.…”
mentioning
confidence: 99%
“…The fused- hgcAB of Pyrococcus furiosus has been experimentally shown not to methylate Hg II (aq) ( Podar et al 2015 ), but the functionality of other fused- hgcAB genes, as well as other members of this clade, is yet to be confirmed. For example, Nitrospina -like hgcA sequences have been reported as the dominant hgcA homologs in many marine environments ( Gionfriddo et al 2016 ; Tada et al 2020 , 2021 ; Villar et al 2020 ). However, the functionality of these sequences has not yet been experimentally confirmed, as no known hgc + members of this genus are currently held in isolation.…”
Section: Resultsmentioning
confidence: 99%
“…The fused hgcAB of Pyrococcus furiosus has been experimentally shown not to methylate Hg II (aq) (Podar et al 2015), but the functionality of other fused- hgcAB genes, as well as other members of this clade, is yet to be confirmed. For example, Nitrospina-like hgcA sequences have been reported as the dominant hgcA homologs in many marine environments (Gionfriddo et al 2016; Tada et al 2020; Villar et al 2020; Tada et al 2021). However, the functionality of these sequences has not yet been experimentally confirmed, as no known hgc + members of this genus are currently held in isolation.…”
Section: Resultsmentioning
confidence: 99%